Persamaan Logaritma Berbentuk a log f(x) = a log g(x) - Anisa Syairah (Jurnal Pustaka Cendekia Pendidikan, 2025)
Logarithms are the opposite of exponents. For this reason, before discussing logarithms, it is necessary toreview exponentials and their properties (Thamrin, 2017). Logarithmic equations are equations whose numbersare logarithmic numbers. Logarithmic equations, in general to solve logarithmic equations related tologarithms, the concept or fact is often used that ???? ???????????? ???? = ???? ???????????? ???? ↔ ???? = ????. The information collectionmethod used is a literature study. By proving the work on the example problem of logarithm equations in theform ???????????????? f(????) = ???????????????? ????(????).